A Star God Is Born: Chintaku Reifujin Talismans in Japanese Religions - Kim, Sujung (Religions, 2022)
This article examines a talismanic culture in Japanese religions through the case of the Chintaku reifu 鎮宅霊符 ("numinous talismans for the stabilization of residences"). Whereas previous scholarship viewed the set of seventy-two talismans as having an ancient Korean origin or connection to the Onmyōdō 陰陽道 tradition in Japan, my analysis of the talismans suggests that they arrived in Japan directly from Ming China around the late Muromachi period. Once introduced, the talismans were widely adopted across different religious traditions such as Buddhism, Shinto, Confucianism, and Shugendō under the name Chintaku reifujin 鎮宅霊符神 (the god of Chintaku reifu talismans) in Japan. Locating the talismans as a major force that shaped the medieval and early modern Japanese religious landscape, this article argues that the worship was not an extension or variation of Chinese Big Dipper worship but a sophisticated form of religious mosaic, which allowed an array of different forms of doctrinal thinking, cosmological knowledge, and ritual logics to coexist.